PERSEPSI MAHASISWA DALAM MENILAI KINERJA DOSEN MELALUI EVALUASI UMPAN BALIK DOSEN (EUB) DI AKADEMI SEKRETARI DAN MANAJEMEN BINA INSANI - Kristiana Widiawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2014)
Research conducted to evaluate the performance of lecturer at the Academy of Secretary and Management Bina Insani based on students perceptions. Evaluation is done only emphasizes the perception of students at one of the implementation of Tri Dharma in the field of teaching (education). Aspects of assessment include Personal Aspects, Teaching Techniques, Academic, and Overall. Another goal Performance Evaluation of lecturers, among others, to determine the quality of the teaching faculty, faculty for self-development, to determine the level of satisfaction of students to teaching faculty. In this research, the sampling method used is simple random sampling technique, using descriptive analysis analytically.